2012
DOI: 10.3358/shokueishi.53.157
|View full text |Cite
|
Sign up to set email alerts
|

粒単位検出システムによる2009年度産遺伝子組換えトウモロコシ試料の遺伝子組換えトウモロコシ品種の定量と同定

Abstract: We investigated the GM maize grain content of non-identity preserved (non-IP) maize samples produced in 2009 in the USA using our individual kernel detection system, involving two multiplex qualitative PCR methods coupled to microchip electrophoresis and partially real-time PCR array analysis, to clarify how many GM event maize grains were present in the samples and which GM events frequently appeared in 2009. The average percentage and standard deviation of GM maize grains on a kernel basis in five non-IP sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 6 publications
(17 reference statements)
0
13
0
Order By: Relevance
“…The National Agricultural Statistics Service (NASS) reported that the percentage of stacked GM maize events has consecutively increased from 1 % in 2000 to 71 % in 2013 in the USA [43]. Indeed, our previous studies showed that the percentage of stacked GM maize events in non-IP samples imported to Japan from the USA increased from 12 % in 2005 [24] to 35 % in 2009 [25]. Judging from these data, almost all GM maize is composed of stacked GM maize events, indicating that no single GM maize events will be distributed commercially in the future.…”
Section: Gmo Content In Test Samplesmentioning
confidence: 92%
See 3 more Smart Citations
“…The National Agricultural Statistics Service (NASS) reported that the percentage of stacked GM maize events has consecutively increased from 1 % in 2000 to 71 % in 2013 in the USA [43]. Indeed, our previous studies showed that the percentage of stacked GM maize events in non-IP samples imported to Japan from the USA increased from 12 % in 2005 [24] to 35 % in 2009 [25]. Judging from these data, almost all GM maize is composed of stacked GM maize events, indicating that no single GM maize events will be distributed commercially in the future.…”
Section: Gmo Content In Test Samplesmentioning
confidence: 92%
“…The discrepancy between ideal and experimental values has been previously reported [2,31] and may be due to differences in PCR efficiencies resulting from the amount of non-targeted sequences in plasmid and genomic DNA [2] or due to differences in the efficiency of DNA extraction between reference and trait genes [31]. GM maize imported to Japan contains not only single GM maize events having a single copy of the trait gene per genome, but also stacked GM maize events having multiple copies of the trait gene per genome as previously reported [25]. The corrected C f values for each trait gene were required to calculate GMO contents in maize samples containing GM maize events having multiple copies of the trait gene per genome, because GMO content is overestimated using the C f value calculated from each GM maize event having a single copy of the trait gene per genome.…”
Section: Measurement Of Conversion Factormentioning
confidence: 92%
See 2 more Smart Citations
“…Thus, rapid and sensitive methods of detecting GMOs are required to allow timely and accurate labeling (Valdés and others ; Milavec and others ; Fraiture and others ). PCR‐CE‐based procedures have been assessed as competitive methods of detecting GMOs because they have high sensitivity, high throughput, and high speed (Burrell and others ; Akiyama and others ; Stojkovic and others ). MSPE‐PCR‐CE was used to successfully detect GM soybeans, which demonstrated its potential for GMO analysis (Jiang and others ; Deng and others ).…”
Section: Procedures For Food Analysis Based On Ce‐based Nucleic Acid Dmentioning
confidence: 99%